Contrast Response Functions for Single Gabor Patches: ROI-Based Analysis Over-Represents Low-Contrast Patches for GE BOLD - Schumacher, Jennifer F.; Thompson, Serena K.; Olman, Cheryl (Frontiers in Systems Neuroscience, 2011)
Important for the interpretation of BOLD fMRI data is a linear relationship between the BOLD response and the underlying neural activity: increased BOLD responses should reflect proportionate increases in the underlying neural activity. While previous studies have demonstrated a linear relationship between the peak amplitude of the BOLD response and neural activity in primary visual cortex (V1), these studies have used stimuli that stimulate large areas of cortex, and the linearity of the BOLD response has not been demonstrated when only a small patch of cortex is stimulated. The BOLD response to isolated Gabor patches of increasing contrast was measured with gradient echo (GE) BOLD and spin echo (SE) BOLD at 7 Tesla. Our primary finding is notable spatial heterogeneity of the BOLD contrast response, resulting in a more reliably linear relationship between BOLD data and inferred neural responses in the center of the cortical representations of the individual Gabor patches than near the edges. A control experiment with larger sinusoidal grating patches confirms that the observed sensitivity to voxel selection in the ROI-based analysis is unique to the small stimuli.